One-Pot Chemoselective Synthesis of Arylated Benzo[h]quinolines - Singh, Surjeet; Yadav, Pratik; Sahu, Satya Narayan; Sharone, Ashoke; Kumar, Brijesh; Ram, Vishnu Ji; Pratap, Ramendra (Synlett, 2014)
A one-pot chemoselective synthesis of 2-aminobenzo[h]quinolines has been delineated by the reaction of 6-aryl-4-sec-amino-2H-pyran-2-one-3-carbonitriles and 2-cyanomethylbenzonitrile using sodamide as a base in DMF. The synthesis involves sequential intermolecular C–C and intramolecular C–C and C–N bond formation. This reaction has delivered benzo[h]quinolines chemoselectively in excellent yield under microwave irradiation. The structure of one product was confirmed by single-crystal X-ray crystallography.
Keywords: chemoselectivity; quinolones; fused-ring systems; nucleophiles